2012
DOI: 10.1227/neu.0b013e31824d18ae
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Central Canal Occlusion Induces Noncommunicating Syringomyelia

Abstract: The proposed MP-SWI demonstrates the feasibility of simultaneously visualizing nerves and vessels of the lower extremities without using an exogenous contrast agent. It may enable straightforward localization of a disease process to a specific nerve and vessel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…In our study, ependymal cells increased with the development of syringomyelia, which confirmed previous findings [13]. On the one hand, our results indicate that ependymal cells play an important role in the pathophysiological process of syrinx formation; on the other hand, ependymal cell proliferation may also be one of the secondary pathological results of syringomyelia.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, ependymal cells increased with the development of syringomyelia, which confirmed previous findings [13]. On the one hand, our results indicate that ependymal cells play an important role in the pathophysiological process of syrinx formation; on the other hand, ependymal cell proliferation may also be one of the secondary pathological results of syringomyelia.…”
Section: Discussionsupporting
confidence: 92%
“…These diseases all lead to changes in the fluid dynamics of CSF in the subarachnoid space, thus favoring the flow of CSF from the subarachnoid space into the central canal [ 29 , 30 ]. Some studies have confirmed that CSF passes through the spinal cord to communicate between the subarachnoid space and central canal [ 13 , 26 , 31 33 ]. In our model, CSF flow was blocked due to extradural compression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 3 Therefore, canicular syringomyelia is closer to hydromyelia, which is similar to subacute or chronic non-communicating hydrocephalus. 27 …”
Section: Discussionmentioning
confidence: 99%